2016
DOI: 10.1371/journal.pone.0168468
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Dosage without Loading Dose Is Efficacious when Treating Carbapenem-Resistant Acinetobacter baumannii Ventilator-Associated Pneumonia Caused by Strains with High Susceptibility to Colistin

Abstract: ObjectivesThis study aims to analyze the mortality and the length of ICU stay (LOS) of A. baumannii VAP compared to respiratory colonization in patients with mechanical ventilation (MV).MethodsA prospective cohort study was performed in an ICU of adult patients (February 2010–June 2011). One hundred patients on MV with A. baumannii in lower respiratory airways were recruited, and classified as VAP or airways colonization according to CPIS criteria, with a punctuation ≥6. LOS, 30-days mortality, A. baumannii ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…These results were not significantly different, perhaps because the minimal inhibitory concentration in our study was low (0.064–1.5) in both groups. These results were supported by Álvarez-Marín et al 15 who showed that non-loading dose of colistin was effective for treating CRAB ventilator-associated pneumonia caused by strains with high susceptibility to colistin. 15 …”
Section: Discussionsupporting
confidence: 54%
“…These results were not significantly different, perhaps because the minimal inhibitory concentration in our study was low (0.064–1.5) in both groups. These results were supported by Álvarez-Marín et al 15 who showed that non-loading dose of colistin was effective for treating CRAB ventilator-associated pneumonia caused by strains with high susceptibility to colistin. 15 …”
Section: Discussionsupporting
confidence: 54%
“…The remaining 98 full-text articles were assessed for eligibility. Nineteen studies [11][12][13]19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] were included in the systematic review based on the inclusion and exclusion criteria. The detailed process of search and selection is shown in Fig 1.…”
Section: Flow Of Included Studiesmentioning
confidence: 99%
“…We identified 22 studies, 16 of which were observational studies [4459], five were randomized clinical trials [6064], and one was systematic review and meta-analysis [65] (Table 2). The studies were based on populations with different sites of infection (airways, bloodstream, abdomen, skin, and meninges) and study population size varying from 10 to 250 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the studies were often based on small sample sizes, reducing the ability to find any effect difference and to consider confounder adjustment and multivariate regression analysis. Only a few studies [24, 25, 34, 36, 40, 44, 47, 51, 52, 54, 55, 64] presented a sample size estimation and adhered to it.…”
Section: Discussionmentioning
confidence: 99%